A Randomized, Double-Blind Study Assessing Changes in Cognitive Function in Indian School Children Receiving a Combination of Bacopa monnieri and Micronutrient Supplementation vs. Placebo - Mitra-Ganguli, Tora; Kalita, Soumik; Bhushan, Sakshi; Stough, Con; Kean, James; Wang, Nan; Sethi, Vidhu; Khadilkar, Anuradha (Frontiers in Pharmacology, 2017)
Several studies have indicated a chronic cognitive enhancing effect of Bacopa monnieri across different ages and cognitive impairment associated with vitamin and mineral deficiencies in children. Therefore, we investigated the effects of 4-month supplementation with a combination of Bacopa monnieri extract and multiple micronutrients on cognitive functions in Indian school children aged 7–12 years. This was a randomised, double-blind, parallel design, single-centre study in which 300 children were randomised to receive a beverage either fortified with Bacopa monnieri and multiple micronutrients (‘fortified’) or a non-fortified isocaloric equivalent (‘control’) twice-daily for 4 months. Cognitive function was assessed by the Cambridge Neuropsychological Automated Test Battery (CANTAB) administered at baseline, Day 60 and Day 121. The primary endpoint was change in short-term memory (working memory) from baseline in subjects receiving ‘fortified’ versus ‘control’ beverages after 4 months. Secondary endpoints included sustained attention, episodic memory and executive function. The ‘fortified’ beverage did not significantly improve short-term memory or any of the secondary outcomes tested relative to the ‘control’ beverage. However, the spatial working memory ‘strategy’ score showed significant improvement on Day 60 (difference between groups in change from baseline: -0.55; p<0.05), but not on Day 121 due to the active intervention. Study products were well tolerated. Reasons for these unexpected findings are discussed.